Exploring aneuploidies in two-center isolated bovine embryonic stem cell lines: Implications for cultured meat production - Chloë Deelkens; Elly De Vlieghere; Mario Van Poucke; Masaki Kinoshita; Jeffrey Aalders; Lieven Thorrez; Bert Devriendt; Ann Van Soom; Luc Peelman; Björn Menten; Catharina De Schauwer; Jolanda van Hengel (Future Foods)
As the global population continues to grow, the demand for sustainable food production methods becomes increasingly critical. This study investigates the presence of chromosomal abnormalities in bovine embryonic stem cells (bESCs), which hold potential for innovative food sources such as cultured meat. We derived three bESC lines from day-eight post-insemination blastocysts using a whole blastocyst plating approach. These cells maintained core pluripotency markers (POU5F1, SOX2, SALL4, NANOG) and demonstrated the ability to differentiate into the three germ layers, indicating their potential for sustainable food applications. Through shallow whole-genome sequencing, we identified various chromosomal anomalies, including mono-, tri-, and tetrasomies, with specific gains in chromosomes 7, 12, 27, and 29, and losses in chromosome 9. Notably, these aneuploidies progressively accumulated over time, raising concerns about genomic stability in long-term cultures. The implications of these genomic variants are significant for the development of cultured meat, as they may affect the efficiency and safety of production processes. This research underscores the necessity for systematic monitoring and optimizing culture conditions to mitigate genomic instabilities, ensuring the safe application of bESCs in sustainable food systems. Our findings pave the way for future innovations in clean food processing and utilising new food ingredients.